The Non-Standard Monetary Policy Measures of the ECB: Motivations, Effectiveness and Risks - Stefano Neri; Stefano Siviero (Credit and Capital Markets – Kredit und Kapital, 2018)
This paper examines the challenges faced by the European Central Bank since the outbreak of the global financial crisis. From 2008 to 2014, the need to preserve the correct functioning of the monetary policy transmission mechanism and ensure the supply of credit to the private sector stretched the limits of conventional monetary policy. In 2015, the risk of deflation led the ECB to start a large scale asset purchase programme. The analysis is largely based on a review of the many studies that Banca d'Italia staff has produced on the factors that have brought inflation to unprecedented low levels in 2014 and on the effects of the asset purchase programme. – – Dieser Beitrag untersucht die Herausforderungen, vor denen die Europäische Zentralbank seit dem Ausbruch der globalen Finanzkrise steht. Von 2008 bis 2014 hat die Notwendigkeit, das ordnungsgemäße Funktionieren des geldpolitischen Transmissionsmechanismus zu wahren und die Kreditversorgung des privaten Sektors sicherzustellen, die Grenzen der konventionellen Geldpolitik überschritten. Im Jahr 2015 führte das Deflationsrisiko dazu, dass die EZB ein groß angelegtes Anleihenkaufprogramm aufnahm. Die vorliegende Analyse basiert im Wesentlichen auf einer Überprüfung der zahlreichen Studien, welche die Mitarbeiter der Banca d'Italia zu den Faktoren erstellt haben. Diese Faktoren haben einerseits die Inflation 2014 auf ein beispiellos niedriges Niveau gebracht und andererseits Auswirkungen auf das Programm zum Ankauf von Vermögenswerten zur Folge gehabt.
Keywords: E31; E43; E52; 330; monetary policy; global financial crisis; sovereign debt crisis; deflation; asset purchases